(untitled) (LEGAL DIALOGICA, 2025)
The purpose of the study was to understand and analyze how legal regulations govern smoking behavior while driving motor vehicles on the highway and the form of criminal liability for drivers who smoke on the highway. Based on the results of the study, the conclusion was obtained, namely the regulation regarding legal liability for drivers who smoke on the highway, the lack of public awareness of traffic regulations can be seen from the low level of public discipline in driving so that it is necessary to create safe, orderly, and smooth transportation services. The regulation also aims to Regulation of the Minister of Transportation Number 12 of 2019 concerning Protection of Public Safety and Interests, namely in Article 6 letter c which states that "drivers are prohibited from smoking and carrying out other activities" that interfere with concentration while driving. In addition, the form of criminal liability is the entire basis and rules adopted by a country in organizing legal order. Abstrak: Tujuan penelitian untuk memahami dan menganalisis bagaimana regulasi hukum yang mengatur perilaku merokok saat mengendarai kendaraan bermotor di jalan raya dan bentuk pertanggungjawaban pidana terhadap pengendara yang merokok di jalan raya. Berdasarkan hasil penelitian, maka diperoleh Kesimpulan yaitu regulasi mengenai pertanggungjawaban hukum terhadap pengendara yang merokok di jalan raya kurangnya kesadaran masyarakat terhadap peraturan berlalu lintas dapat dilihat dari rendahnya tingkat kedisiplinan masyarakat dalam berkendara sehingga perlu untuk menciptakan pelayanan transportasi yang aman, tertib, dan lancar. Peraturan tersebut juga bertujuan untuk Peraturan Menteri Perhubungan Nomor 12 Tahun 2019 Tentang Perlindungan Keselamatan Kepentingan Masyarakat yaitu pada Pasal 6 huruf c yang menyatakan bahwa “pengemudi dilarang merokok dan melakukan aktifitas lain” yang mengganggu konsentrasi ketika sedang mengendarai. Selain itu bentuk pertanggungjawaban pidana ialah keseluruhan dasar-dasar dan aturan-aturan yang dianut oleh suatu negara dalam menyelenggarakan ketertiban hukum.